Medical service quality, Dimensions the quality of service, satisfaction with medical service - النعيمي, شهاب الدين حمد; زيدان, حسين غازي (Journal of Economics and Administrative Sciences, 2016)
the Objective of  study is  to measure the quality of medical service level,  in the  Iraq public hospitals ,presented by  special words ,private hospitals, and compare between them, by knowing the level of recipients satisfaction  of medical service for all dimensions of quality service, and then measuring satisfaction with the quality of medical service as a whole for both of them, which have been prepared in questionnaire form, included two main directions, first to determine the level of satisfaction when, recipients of medical service is not dimensions quality of service in accordance with the Scale Servqual by (Parasurman et .al 1988), consisting of five dimensions (reliability, responsiveness, courtesy, safety and tangibility) and amounted to 45 the number of questions asked by (9) questions after each of these dimensions, The second trend has been included on the knowledge level of satisfaction when the recipient of the medical service, and general satisfaction with them, include(8) questions. The most important conclusions represented by that satisfaction recipients of medical services, from government own word are more than that satisfied with the private hospitals, The most important recommendations are need first private suites in government hospitals to do a propaganda campaign in order change in the impression of bad firm among the level of provided medical service at public hospital , second to have more attention in immediate ambulance services and emergency